Estação para carga de dispositivos móveis utilizando energia solar - Lira, Lorena Gabriela de Góis (Universidade Federal Rural do Semi-Árido, 2019)
The objective of the present work was the development of a station for charging mobile devices, driven by the need to perform several daily tasks aggregated to the device. With the advance of tablets, smartphones and consequently of the applications, the population has been performing these tasks through them, besides the usual use for communication in general. With the intensification in the use of these devices, the batteries will require more and more load throughout the day (or have a greater capacity in the storage of energy), especially the worn ones. For this reason, the study of the methods for the development of a charging station for mobile devices, with the use of solar energy. Based on specifications of a photovoltaic board, a bucktype DC-DC converter was designed to control the voltage and current levels required for the load. The project was accomplished through mathematical calculations, simulation in the PSIM software and the creation of a benchtop prototype. The results were satisfactory, with approximate values and the converter acted effectively.
Monografia
Keywords: Dispositivos móveis; Baterias; Energia solar; ENGENHARIAS::ENGENHARIA ELETRICA